Tolerance of wheat cultivars to different levels of manganese in nutrient solution - Camargo, Carlos Eduardo de Oliveira; Ferreira, Antonio Wilson Penteado (Pesquisa Agropecuaria Brasileira, 1992)
Twenty six wheat culivars were studied for manganese tolerance in nutrient solution. The treatments consisted of four manganese levels 0.11, 300, 600 and 1,200 mg/l, under constant temperature, 25±1°C, pH 4.8, and continuous aeration. Manganese tolerance was evaluated by considering the mean root length, for each cultivar, after a period of twelve days growing in nutrient solution with different manganese levels. The cultivars IAC-24, OCEPAR-7, Alondra-S-46, IAC-161, IAC-162, Cotiporã and IAPAR-17 were as tolerant or more tolerant than the cultivar Siete Cerros, used as a control and may be considered genetic sources of high value for breeding programs. The most sensitive cultivars were IAC-18 and IAC-21 considered as sensitive as the control (cultivar BH-1146). The cultivars IAC-29, CEP 7780, IAC-25, IAC-60, IAC-74, IAC-5, IAC-17, Anahuac, IAC-227, PAT-72247, IAC-18, Carazinho, OCEPAR-11, IAC-27 and IAC-72 exhibited moderate tolerance to manganese toxicity. The cultivars IAC-24 and Cotiporã, showing tolerance to manganese and aluminum toxicities, are adequate germplasms for cultivation in acid soils.